Cultural practices in the nursery that affect seedling quality of Enterolobium cyclocarpum - Basave Villalobos, Erickson; López López, Miguel Á; Cetina Alcalá, Víctor M; Aldrete, Arnulfo; Almaraz Suárez, Juan J (Bosque (Valdivia), 2017)
Because one of the main problems that Enterolobium cyclocarpum faces in the planting site is the presence of weeds, to grow plants presenting appropriate characteristics that enable them to overcome these adverse conditions during reforestation appears as necessary. Therefore, after evaluating the responses of various morphological and physiological indicators, and a quality test experiment, the effects of three top pruning intensities (no pruning, 25 % and 50 % pruning) and three fertilization regimes (traditional, exponential and conventional) were studied during nursery production. This approach was made based on the fact that top pruning and fertilization in the nursery are cultural practices that improve seedling quality as long as the pruning intensity and fertilization regime are appropriate. There was no synergy between the two practices; however, each factor influenced independently on the indicators evaluated. Top pruning at 25 % and 50 % did not improve the characteristics of E. cyclocarpum. However, the nutrient supply in a conventional way had a favorable effect when compared with other fertilization regimes. The results provided by the quality test established that conventional fertilization allows plants to perform satisfactorily when nutrient availability is limited.